Ungleiche Entwicklung in Zentraleuropa Überregionale Arbeitsteilung und imperiale Politik - Kaps, Klemens (2015)
The Habsburg crownland Galicia was one of the poorest region of the Habsburg Monarchy and could in the 19th century only rudimentarily catch up with industrialization and income growth of other regions. The book shows how over the long run the unequal transregional entanglements, in particular concerning commodity trade, alongside with the imperial economic policy restrained Galicia's economic development between 1772 and 1914.